MEANING DECONSTRUCTION OF YOU’LL NEVER WALK ALONE AND GLORY GLORY MAN UNITED - Susanto, Kelvin Abednego; Handayani, Lucia Lusi Ani (UI Scholars Hub, 2021)
Nowadays, the soccer world has been developing rapidly, particularly in Europe. In one of its countries, England, there are two notable soccer clubs that are worth discussing. They are Liverpool Football Club and Manchester United Football Club. These clubs have a considerable number of fans among all around the world. Also, they have anthems that are often sung by the fans. Their anthems are “You’ll Never Walk Alone” and “Glory Glory Man United.” These anthems are important because they give impacts both on the teams and on the fans. This study specifically discusses the underlying meanings within both anthems. They are revealed through the words, phrases, and sentences in the lyrics of the anthems. To do so, library research method is used. Interestingly, this study has found that associative meaning and figurative language are used frequently by songwriters to aestheticize words, phrases, and sentences used to express their aims. Therefore, it can be inferred that anthems are not only used for showing the identity of a soccer club, but also for giving support towards the home teams, yet become pressure towards the opposition teams at the same time.